Gold Nanoparticles Decorated Two-Dimensional tio2 Nanosheets as Effective Catalyst for Nitroarenes and Rhodamine B Dye Reduction in Batch and Continuous Flow Methods - Singh, D (Elsevier B.V., 2023)
Our environment is greatly endangered by the accumulation of various toxic organic pollutants that are continually produced through unavoidable human needs and the industrialization process. Herein, we report highly active gold nanoparticles (AuNPs) immobilized on two-dimensional (2D) TiO2 nanosheets (AuNPs-TiO2NSs) as a catalyst for the catalytic reduction of nitroarenes (NAs) such as 4-nitroaniline (4-NA), 4-(4-nitrophenyl)morpholine (4-NM), 4-(2-fluoro-4-nitrophenyl)morpholine (4-FNM) and rhodamine B (RhB) dye in the presence of sodium borohydride (NaBH4) medium. Initially, TiO2NSs are prepared by the hydrothermal treatment followed by the modification with 3-aminopropyl-trimethoxysilane (APTMS) coupling agent for strong anchoring of the AuNPs. HR-TEM images exhibit that AuNPs (2.30 ± 0.06 nm) are immobilized on the surface of ultrathin 2-dimensional TiO2NSs. AuNPs-TiO2NSs catalyst shows excellent catalytic activity towards the reduction of various NAs (4-NA, 4-NM and 4-FNM) and RhB dye with maximum conversion efficiency of >98 %. Moreover, the pseudo-first-order rate constants are estimated as 5.50 × 10−3 s−1, 7.20 × 10−3 s−1, 6.40 × 10−3 s−1 and 4.30 × 10−3 s−1 for the reduction of 4-NA, 4-NM, 4-FNM, and RhB, respectively. For large-scale industrial applications, AuNPs-TiO2NSs catalyst embedded in a continuous flow-fixed bed reactor for the catalytic reduction of 4-NA and RhB dye under optimized reaction conditions. AuNPs-TiO2NSs catalyst shows high conversion rates for 4-NA (>99 %) and RhB (>99%) along with excellent recyclability over 12 cycles in continuous flow fixed bed reactor. The mechanism of synthetic pathway and catalytic reduction of NAs and RhB dye over AuNPs-TiO2NSs catalyst are also proposed. This study may lead to the use AuNPs-TiO2NSs catalyst with superior recyclable catalytic efficiency in various catalytic reactions. © 2023 Elsevier B.V.